(untitled) (Itinera, 2018)
This essay traces Derrida’s interrogation of Nietzsche and Freud’s concept of cruelty and his attempt to think the beyond that this concept necessarily presupposes. On the one hand, it highlights the key traits of the Nietzschean and Freudian concept of cruelty, namely, its irreducibility to determination and its essential entanglement with life. On the other hand, it explains that the beyond cruelty, which Derrida thinks by dissociating life from cruelty, offers us the point of departure for another thinking of life as well as for the foundation of the right to life.